A design methodology for passive mechatronic vibration absorbers. (January 2022) - Yuan, Hui; Li, Yuan; Jiang, Jason Zheng; Al Sakka, Monzer; Dhaens, Miguel; Burrow, Steve; Gonzalez-Buelga, Alicia; Clare, Lindsay; Mellor, Phil
Abstract: Passive mechatronic vibration absorbers have demonstrated great performance potential in previous studies. For such devices, optimal design of the electrical circuits therein is critical but challenging since existing techniques have evident limitations: those investigating a few specific circuits leave huge possibilities unexplored; those optimising circuit impedances potentially lead to circuits which cannot be physically implemented. Another challenge lies in the need for considering device parasitic effects (e.g., transducer 1 resistance) to guarantee the predicted performance accuracy—this can be extremely time-consuming, especially when exploring numerous design possibilities (e.g., circuits, transducers). To address these two challenges, this paper proposes a novel design methodology, which (1) allows the optimal and practically implementable circuit to be identified among all layouts with predefined complexity; (2) considers the device parasitic effects where necessary, to efficiently explore various possibilities. The validity of this methodology is demonstrated via an automotive suspension design case study, where the obtained significant performance improvement is successfully verified via experiments. This methodology is directly applicable to vibration suppression of other engineering structures and can also be adopted for other mechatronic absorber types. Highlights: A novel design methodology for passive mechatronic vibration absorbers is proposed. Total electrical circuit possibilities with predefined complexity can be explored. Optimal circuit with realistic element values can be identified. Parasitic effects are considered in a controlled way for efficient design process. The methodology is validated via an automotive suspension design case study.